Convergent variational calculation of positronium-hydrogen-atom scattering lengths - Adhikari, S. K.; Mandal, P. (Iop Publishing Ltd, 2001)
We present a convergent variational basis-set calculational scheme for elastic scattering of the positronium atom by the hydrogen atom in S wave. Highly correlated trial functions with appropriate symmetry are needed to achieve convergence. We report convergent results for scattering lengths in atomic units for both singlet (= 3.49 +/-0.20) and triplet (= 2.46 +/-0.10) states.